The Interplay of Sound Tapestry and Music in the 1992 German Radio Play Adaptation of J.R.R. Tolkien’s The Lord of the Rings - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama: An Introduction - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

Fast model-based calibration of multiple injections for a CI engine using nonlinear optimal control - Moretto, Giordano; Schnell, Nicolas; Frey, Jonathan; Karakaya, Yasin; Amstutz, Alois; Diehl, Moritz; Kasper, Tina; Onder, Christopher (Control Engineering Practice)

Gottes Treue zu Israel (Röm 9–11) - Taschl-Erber, Andrea; Woppowa, Jan (Elementare Bibeltexte)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

Stickstoff basierte Flammschutzmittel für das Lasersintern: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Hücker, Lars

Phosphorhaltige Lasersinter-Materialien mit Flammschutzwirkung: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Schulz, Maurice

Einfluss von Temperatur und Strömungsführung auf die NH3-SCO sowie die NH3-SCR mit Partikeln aus einer Sprayflammensynthese - Bablitzka, Nico Janosch; Beimdiek, Janis

Evaluation of Surrogate Aerosol Experiments to Predict Spreading and Removal of Virus-Laden Aerosols - Beimdiek, Janis; Schmid, Hans-Joachim (Atmosphere)
Estimating the infection risks in indoor environments comprises the assessment of the behavior of virus-laden aerosols, i.e. spreading, mixing, removal by air purifiers etc. A promising experimental approach is based on using non-hazardous surrogate aerosols of similar size, e.g. salt particles, to mimic the virus aerosol behavior. This manuscript addresses the issue how a successful transfer of such experiments can be accomplished. Corresponding experiments in two very different environments, a large community hall and a seminar room, with optional use of air purifiers in various constellations were conducted. While high particle concentrations are advantageous in terms of avoiding influence of background aerosol concentrations, it is shown that appropriate consideration of aggregation and settling are vital to theoretically describe the experimentally determined course of particle concentrations. A corresponding model equation for a well-mixed situation is derived and the required parameters are thoroughly determined in separate experiments independently. It is demonstrated that clean air delivery rates (CADR) of air purifiers determined with this approach may differ substantially from common approaches not explicitly taking into account aggregation.
Keywords: surrogate aerosols; indoor air cleaners; ultra-fine particles; COVID-19; test method; field experiments: clean air delivery rate

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Single-step self-punching lockbolt process for aluminum sheets without pre-hole - Han, Daxin; Kappe, Fabian; Vorderbrüggen, Julian; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Methodenentwicklung zur rechnerischen Auslegung geklebter Stahlverbindungen unter Alterungsbeanspruchung im Stahl- und Anlagenbau - Beule, Felix; Sander, Sascha; Meschut, Gerson; Damm, Jannis; Kasper, Yann; Albiez, Matthias; Kötz, Fabian; Matzenmiller, Anton (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Klebstoffmodell - Parameteridentifikation, Verifikation und Validierung für den Lastfall Crash - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (DECHEMA-Workshop für Klebstoffanwender: Simulation von Klebverbindungen)

Methodenentwicklung zur Simulation von hyperelastischen Klebverbindungen unter Crashbelastung - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Schmelzle, Lars; Possart, Gunnar; Mergheim, Julia; Steinmann, Paul

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Multiscale simulation of polymer curing of composites combined mean-field homogenisation methods at large strains - Lenz, Peter; Mahnken, Rolf (International Journal of Solids and Structures)
Keywords: Applied Mathematics; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Carillo Beber, Vinicius; Fernandes, Pedro; Nagel, Christof; Köster, Christian; Matzenmiller, Anton; Hecht, Mathias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Bruchmechanisches Schnittebenenkonzept zur lebensdauergerechten Auslegung von hyperelastischen Klebverbindungen bei multiaxialen und variablen Belastungsamplituden - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson; Buczek, Moritz; Duffe, Tobias; Kullmer, Gunter (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Mechanisches Verhalten: Charakterisierung von Klebstoffen - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

„4 THe BoYZ“ – Widmungen im Szene-Graffiti aus konstruktionsgrammatischer Perspektive. Die multimodale Relator-Konstruktion als grammatische Musterbildung im Horizont des Textes - Tophinke, Doris; Dübbert, Alexander (Konstruktionsgrammatik X. Textsorten und Textmuster als Konstruktionen?)

Perspectives of children and young people on their education as preparing for their future in the digital age: In-depth qualitative study in five European countries. - Eickelmann, Birgit; Barbovschi, M.; Holmarsdottir, H.B.; Parsanoglou, D.; Sisask, M.; Labusch, Amelie (Understanding the everyday digital lives of children and young people)

Evaluation of Surrogate Aerosol Experiments to Predict Spreading and Removal of Virus-Laden Aerosols - Beimdiek, Janis; Schmid, Hans-Joachim (Atmosphere)
Keywords: surrogate aerosols; indoor air cleaners; ultra-fine particles; COVID-19; test method; field experiments: clean air delivery rate

Konzeptentwicklung für ein Stahlbatteriegehäuse unter besonderer Berücksichtigung der Fügetechnik und des Korrosionsschutzes - Chudalla, Nick; Schmolke, Tobias; Meschut, Gerson; Spohr, Sebastian; Eckstein, Lutz; Brunner-Schwer, Christian; Rethmeier, Michael; Nothelfer-Richter, Rolf; Hilt, MIchael (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimental and Theoretical Investigation of CO2 Absorption in Aqueous Solution of Glucosamine: Material Property and Equilibrium Data - Hami Dindar, Iman; Mirzaei, Mona; Baumhögger, Elmar; Lutters, Nicole; Kenig, Eugeny Y. (Journal of Chemical & Engineering Data)
Keywords: General Chemical Engineering; General Chemistry

Dynamics of an Absorption/Desorption Plant: Experimental Study and Model Validation - Weber, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Methodenentwicklung zur Simulation des Viscous Fingering in Klebverbindungen von stahlintensiven Mischbaustrukturen - Al Trjman, Mohamad; Meschut, Gerson; Salten, Alexander Heinrich Johannes; Kenig, Eugeny Y.

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik; Gilich, Julian; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Der Einfluss von Mikrostrukturen auf die Flüssigkeitsausbreitung in strukturierten Packungen - Dechert, Christopher; Kenig, Eugeny

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Wässrige Glucosaminlösung als neues Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y.

Diagnostics of Piezoelectric Bending Actuators Subjected to Varying Operating Conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Hemsel, Tobias; Sextro, Walter (Electronics)
In applications of piezoelectric actuators and sensors, the dependability and particularly the reliability throughout their lifetime are vital to manufacturers and end-users and are enabled through condition-monitoring approaches. Existing approaches often utilize impedance measurements over a range of frequencies or velocity measurements and require additional equipment or sensors, such as a laser Doppler vibrometer. Furthermore, the non-negligible effects of varying operating conditions are often unconsidered. To minimize the need for additional sensors while maintaining the dependability of piezoelectric bending actuators irrespective of varying operating conditions, an online diagnostics approach is proposed. To this end, time- and frequency-domain features are extracted from monitored current signals to reflect hairline crack development in bending actuators. For validation of applicability, the presented analysis method was evaluated on piezoelectric bending actuators subjected to accelerated lifetime tests at varying voltage amplitudes and under external damping conditions. In the presence of a crack and due to a diminished stiffness, the resonance frequency decreases and the root-mean-square amplitude of the current signal simultaneously abruptly drops during the lifetime tests. Furthermore, the piezoelectric crack surfaces clapping is reflected in higher harmonics of the current signal. Thus, time-domain features and harmonics of the current signals are sufficient to diagnose hairline cracks in the actuators.
Keywords: piezoelectric transducer; self-sensing; fault detection; diagnostics; hairline crack; condition monitoring

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Modellbasierte Entwicklung von Ultraschallwandlern unter der Berücksichtigung von Nichtlinearitäten - Dymel, Collin
Ultraschallsysteme für das Herstellen für Bond- und Schweißverbindungen in der Halbleiterfertigung zeigen auf Grund des Betriebes unter hohen Anregungsniveaus nichtlineare Materialeigenschaften. Dabei wirken unterschiedliche Einflussfaktoren auf die elektrischen Eigenschaften und die mechanischen Übertragungscharakteristiken der Ultraschallsysteme ein. Die Herausforderungen ein solches geprägtes System auszulegen oder effizient und zuverlässig zu betreiben, sind aufgrund der Nichtlinearitäten relativ groß. Da für die Beschreibung der nichtlinearen Materialbeziehungen nur wenige Modelle und kaum quantitative Angaben vorliegen, werden die komplexen Wechselwirkungen von Materialparametern, Geometrie und Vorspannung des Schwingers, Betriebsgrößen (Strom, Spannung), Temperatur und Prozesslasten durch systematische Untersuchungen von Keramiken und Langevin-Schwingern messtechnisch erfasst. Aus den Messergebnissen werden einerseits eindimensionale Modelle für Voruntersuchungen als auch vollständige Materialparametersätze für die Simulation mittels dreidimensionaler FE-Modelle hergeleitet. Eine Methodik zur Ermittlung der Materialparameter und ein auf iterativen Simulationen von FE-Modellen basierendes Werkzeug zur Simulation der komplexen Wechselwirkungen werden vorgestellt. Anhand eines exemplarischen Ultraschallsystems wird gezeigt, dass die Wirkungen temperaturbedingter Vorspannungsverluste, Änderungen des elektrischen Klemmenverhaltens und Amplituden- und Frequenzänderungen während des Betriebes bei großen Amplituden und Prozesslasten durch die Variationen des Keramikvolumens und der Keramikposition positiv beeinflusst werden können.
Keywords: Nichtlineares piezoelektrisches Verhalten; Dehnungsabhängigkeit; Vorspannungseinfluss; Temperatureinfluss; Lasteinfluss; Langevin-Schwinger; Ultraschallwandler; Ultraschallbonden; FEM-Modell; Ultraschallschweißen; BVD-Modell

Influences of Weld Nugget Shape and Material Gradient on the Shear Strength of Resistance Spot‐Welded Joints - Schuster, Lilia; Olfert, Viktoria; Sherepenko, Oleksii; Fehrenbach, Clemens; Song, Shiyuan; Hein, David; Meschut, Gerson; Biro, Elliot; Münstermann, Sebastian (steel research international)
Resistance spot‐welded joints containing press‐hardened steels are seen to exhibit a fracture mode called total dome failure, where the weld nugget completely separates from one steel sheet along the weld nugget edge. The effect of weld nugget shape and material property gradients is studied based on damage mechanics modeling and experimental validation to shed light on the underlying influencing factors. For a three‐steel‐sheet spot‐welded joint combining DP600 (1.5 mm)–CR1900T (1.0 mm)–CR1900T (1.0 mm), experiments under shear loading reveal that fracture occurs in the DP600 sheet along the weld nugget edge. In subsequent numerical simulation studies with damage mechanics models whose parameters are independently calibrated for every involved material configuration, three variations of the geometrical joint configuration are considered—an approximation of the real joint, one variation with a steeper weld nugget shape, and one variation with a less pronounced gradient between weld nugget material and heat‐affected zone material properties. The results of the finite‐element simulations show that a shallower weld nugget and a more pronounced material gradient lead to a faster increase of plastic strain at the edge of the weld nugget and promote the occurrence of total dome failure.
Keywords: Materials Chemistry; Metals and Alloys; Physical and Theoretical Chemistry; Condensed Matter Physics

Zur Abscheidung von Tröpfchen-Aerosolen in filternden Abscheidern - Hassel, Richard

Untersuchung des Lösungsmitellseinflusses auf die Synthese von Manganoxid-Nanopartikeln in der Flammenspraypyrolyse - Zink, Timm Florian

Construction of A-stable explicit last-stage diagonal implicit Runge–Kutta (ELDIRK) methods - Mahnken, Rolf; Westermann, Hendrik (Computational Mechanics)
ELDIRK methods are defined to have an Explicit Last stage in the general Butcher array of Diagonal Implicit Runge-Kutta methods, with the consequence, that no additional system of equations must be solved, compared to the embedded RK method. Two general formulations for second- and third-order ELDIRK methods have been obtained recently in Mahnken [21] with specific schemes, e.g. for the embedded implicit Euler method, the embedded trapezoidal-rule and the embedded Ellsiepen method. In the first part of this paper, we investigate some general stability characteristics of ELDIRK methods, and it will be shown that the above specific RK schemes are not A-stable. Therefore, in the second part, the above-mentioned general formulations are used for further stability investigations, with the aim to construct new second- and third-order ELDIRK methods which simultaneously are A-stable. Two numerical examples are concerned with the curing for a thermosetting material and phase-field RVE modeling for crystallinity and orientation. The numerical results confirm the theoretical results on convergence order and stability.
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

Anisotropic Mechanical and Microstructural Properties of a Ti-6Al-7Nb Alloy for Biomedical Applications Manufactured via Laser Powder Bed Fusion - Milaege, Dennis; Eschemann, Niklas; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
Through tailoring the geometry and design of biomaterials, additive manufacturing is revolutionizing the production of metallic patient-specific implants, e.g., the Ti-6Al-7Nb alloy. Unfortunately, studies investigating this alloy showed that additively produced samples exhibit anisotropic microstructures. This anisotropy compromises the mechanical properties and complicates the loading state in the implant. Moreover, the minimum requirements as specified per designated standards such as ISO 5832-11 are not met. The remedy to this problem is performing a conventional heat treatment. As this route requires energy, infrastructure, labor, and expertise, which in turn mean time and money, many of the additive manufacturing benefits are negated. Thus, the goal of this work was to achieve better isotropy by applying only adapted additive manufacturing process parameters, specifically focusing on the build orientations. In this work, samples orientated in 90°, 45°, and 0° directions relative to the building platform were manufactured and tested. These tests included mechanical (tensile and fatigue tests) as well as microstructural analyses (SEM and EBSD). Subsequently, the results of these tests such as fractography were correlated with the acquired mechanical properties. These showed that 90°-aligned samples performed best under fatigue load and that all requirements specified by the standard regarding monotonic load were met.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Vmin Testing under Variations: Defect vs. Fault Coverage - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Latin American Test Symposium (LATS), Maceió, Brazil, April 9-12, 2024)

Innovative measurement system for saber curvature observation in straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Procedia Computer Science)
Keywords: General Engineering

LiDAR-Sensormodell basierend auf zeitabhängigem Photon Mapping - Bußemas, Leon; Fittkau, Niklas; Gausemeier, Sandra; Trächtler, Ansgar; Rüddenklau, Nico (VDI Mechatroniktagung Dresden 2024)